An Analysis of Hate Speech on Social Media - Cahyani, Arwini Ragita; Mahmud, Murni; Affandi, Akhmad (State University of Makassar, 2026)
This research aims to identify and analyze the forms of hate speech found in comment section of Donald Trump’s official X account and examine how language reflects ideological opposition in online political discourse. This study employs a qualitative descriptive method within framework of Discourse Analysis. The data consist of twenty seven comments collected from Trump’s account between May ad July 2024 by high political tension in the United States. This research also applied typology of hate speech classified by Zembylas into five category: insulting, dehumanizing, stereotype, threatening, and exclusionary hate speech. In general, the purpose of this study is to understand how online users express disagreement and hostility linguistic strategies that reflect their social ideological positions. This research provides insight into how hate speech functions within digital communication as both a reflection of political sentiment and as reinforcement of collective identify. This research also emphasizes the important developing social awareness and digital literacy to reduce hostility and more constructive discourse on social media platforms.Keywords: hate speech, critical discourse analysis, social media, donald trump.